The balneoterapy in complex rehabilitation of patients with coronary heart diseases after surgical myocardial revascularization - Kolodenko, Olena; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Kolodenko Olena, Zukow Walery. Використання бальнеотерапії в комплексному санаторно-курортному лікуванні хворих з ішемічною хворобою серця після хірургічної реваскулярізації міокарду =The balneoterapy in complex rehabilitation of patients with coronary heart diseases after surgical myocardial revascularization. Journal of Education, Health and Sport. 2015;5(10):291-298. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34058 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A291-298 https://pbn.nauka.gov.pl/works/670593 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 25.10.2015. УДК 616.12-005.4+616.37-008.64]-085:615.327 Використання бальнеотерапії в комплексному санаторно-курортному лікуванні хворих з ішемічною хворобою серця після хірургічної реваскулярізації міокарду Использование бальнеотерапии в комплексном санаторно-курортном лечении больных с ишемической болезнью сердца после хирургической реваскуляризации миокарда The balneoterapy in complex rehabilitation of patients with coronary heart diseases after surgical myocardial revascularization Колоденко Олена Володимирівна ДУ «Український НДІ Медичної реабілітації та курортології МОЗ України» (м. Одесса), kolodenkol@ukr.net Olena Kolodenko Ukrainian Research Institute of Medical Rehabilitation and Balneology of Ministry of Health of Ukraine (Odessa) kolodenkol@ukr.net Колоденко Елена Владимировна Украинский НИИ Медицинской реабилитации и курортологии МЗ Украины (г. Одесса) kolodenkol@ukr.net Zukow Walery Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska Zukow Walery Kazimierz Wielki University, Bydgoszcz, Poland Zukow Walery Kazimierz Wielki University, Bydgoszcz, Poland Стаття присвячена питанням використання бальнеотерапії в програмах комплексної санаторно-курортної реабілітації пацієнтів з ішемічною хворобою серця, які перенесли хірургічну реваскулярізацію міокарду. Нами вивчено ефективність використання бальнеокинезотерапії та внутрішнього прийому мінеральної води в комплексній реабілітації цих пацієнтів в умовах санаторію. Доведено ефективність застосування запропонованих комплексів, а саме покращення показників, що відображують толерантність до фізичного навантаження (р<0,05), зниження рівня глюкози натщесерце та через 2 години після їжі, зниження показника інсуліну, нормалізація ліпідного профілю. Ключові слова: реабілітація, ішемічна хвороба серця, хірургічна реваскулярізація міокарду, бальнеокинезотерапія. Статья посвящена вопросам реабилитации пациентов с ишемической болезнью, которые перенесли хирургическую реваскуляризацию миокарда. Нами изучена эффективность использования бальнеокинезотерапии и внутреннего приема минеральной воды в комплексной реабилитации этих пациентов в условиях санатория. Доказана эффективность использования разработанных комплексов, а именно улучшение показателей толерантности к физической нагрузке (р<0,05), достоверное снижение уровня глюкозы натощак и через 2 часа после еды, снижение уровня инсулина, нормализация липидного обмена. Ключевые слова: реабилитация, санаторно-курортное лечение, ишемическая болезнь сердца, хирургическая реваскуляризация миокарда, бальнеокинезотерапия. Introduction: Coronary heart disease (CHD) is one of the most common pathologies of the circulatory system in developed countries. Of all causes of death from cardiovascular diseases coronary heart disease is accounted for 53% of them. Despite the fact that great progress has been made in the surgical treatment of coronary artery disease, its effectiveness is directly related to the quality of postoperative rehabilitation. Even successfully carried myocardial revascularization does not prevent further progression of atherosclerosis, which makes the problem of secondary prevention of coronary heart disease even more important for these patients. This article considers rehabilitation of patients with coronary heart disease and concomitant diabetes mellitus, who underwent surgical myocardial revascularization. Purpose: To develop and examine the effectiveness of complex sanatorium treatment of patients with coronary artery disease after surgical myocardial revascularization. Materials and Methods: We observed 80 patients aged 58,7±8,9 with coronary artery disease, who underwent surgical myocardial revascularization and who were on rehabilitation at the sanatorium. We have developed the complexes of resort treatment for these patients in the resort, which include hydrokinesitherapy in the pool with mineral water and ingestion of mineral water. Discussion: The efficiency of usage of the developed complexes was shown through the improvement of tolerance to physical loading (p<0.05), a significant decrease of fasting plasma glucose level and 2h-after-meal level, reduced insulin levels, normalization of lipid metabolism. As a result of resort treatment a positive effect on carbohydrate metabolism, especially in patients who used mineral water, was observed. The possible reduction in fasting glucose and 2h-after-meal was observed in both groups after resort treatment, namely by 16.9 and 20.3% (in the first group) and 23.7 and 22.4 (in the 2nd group), respectively (p<0.05). A drop in insulin in both groups indicated a positive impact of the treatment with mineral water on the secretory function of the pancreas (19.6 and 37.9%, respectively). Keywords: rehabilitation, resort treatment, coronary heart disease, surgical myocardial revascularization, diabetes mellitus.